Fluctuations in External Peak Demands Across Quarters During Basketball Games - Alonso Pérez-Chao, Enrique; Gómez, Miguel-Ángel; Lisboa, Pedro; Trapero, Juan; Jiménez, Sergio L.; Lorenzo, Alberto (Frontiers in Physiology, 2022)
The aim of this study was to compare the fluctuations in external peak demands (PD) across quarters (Q) during basketball games. There were studied intervals for different time windows to determine the PD for distance (m); player load; distance covered in four different zones, accelerations, and decelerations. Mixed Linear Model was run to identify differences among quarters and the auto-correlation function was carried out to determine fluctuations across the game. The results showed significant differences between Q1 vs Q2 for distance, player load and standing-walking distance; between Q1 vs Q3 for distance, player load and HSR; between Q1vs Q4 for distance, player load, standing-walking, and HSR; and between Q3 vs Q4 for distance, and player load. These findings suggests that external PD for parameters based on running demands (distance, player load and high-speed running) decrease across basketball games with most notable declines occurring between the first and fourth quarters.